Do Gibberellins Mediate Growth Responses of the Halophytic Woody Prosopis Strombulifera (Lam.) Benth Plants Exposed to Different Sodium Salts? - Llanes, Analia Susana (2022)
Phytohormones have essential roles in plant growth responses under salinity. A better understanding of gibberellin (GA) function in woody plant responses under different sodium salts could help to develop new strategies to improve plant tolerance to salinity. In this study, the role of GA in morpho-physiological responses of halophytic woody Prosopis strombulifera plants under salinity was analyzed. Plants were grown in hydroponic solutions and exposed to NaCl, Na2SO4, or their iso-osmotic mixture at − 1.0, − 1.9, and − 2.6 MPa. Control (without salt) and salt-treated plants were sprayed with gibberellin A3 (GA3), or chlormequat chloride (CCC), an inhibitor of its synthesis. Growth responses, anatomical alterations and ABA, active GA forms (GA1, GA3, and GA4) and inactive GA forms (GA8 and GA34) endogenous levels were evaluated. The application of GA3 increased growth in control plants more than in salt-treated plants. Roots and leaves of salt-treated plants showed high levels of ABA and active GA forms after exposure to GA3, and lower endogenous levels of active GA when receiving the inhibitor. CCC triggered stress-alleviating responses in these plants, such as anatomical and hormonal changes that included an increase in spine length and the number of palisade cell layers, and a reduction in levels of ABA and GA4. Na2SO4-treated plants showed reduced growth, high ABA levels and an active GA metabolism to control the levels of active GA. This study indicates that the suppression of GA signaling would contribute to sodium salts tolerance in the native halophytic woody P. strombulifera plants.